Praktyczne aspekty rachunku kosztów w spółdzielniach mleczarskich - Wasilewski, Mirosław; Chmielewska, Marzena (Practical aspects of cost calculation in dairy cooperatives, 2006)
The paper presents the methods of cost accounting and rules of the accounting in dairy cooperatives in Sieradz and Radomsko. In these cooperatives, a traditional calculation of costs and results has been used. Cost evidence has been carried out both in generic and calculation systems. There have been no significant differences in total costs’ structure, although there has occurred different scales of activity in the cooperatives. Moreover, the results of a calculation of productions unit costs of selected products have not illustrated the scale of production. In the dairy cooperatives a conception of full costs accounting was implemented. However, variable costs’ accounting has not been used in the cooperatives’ management yet. The implementation of the accounting would efficiently improve effectiveness of decision-making process concerning the products in assortment structure and production optimizing. In the dairy cooperatives it is necessary to implement controlling procedures for a better source of information, what would probably improve their activity’? effectiveness.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1125, s. 123-137